2009
DOI: 10.1007/s10295-009-0644-6
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose accumulation from corn starch by Saccharomycopsis fibuligera A11 during 2-l fermentation and trehalose purification

Abstract: In this study, corn starch was used as the substrate for cell growth and trehalose accumulation by Saccharomycopsis Wbuligera A11. EVect of diVerent aeration rates, agitation speeds, and concentrations of corn starch on direct conversion of corn starch to trehalose by S. Wbuligera A11 were examined using a Biostat B2 2-l fermentor. We found that the optimal conditions for direct conversion of corn starch to trehalose by this yeast strain were that agitation speed was 200 rpm, aeration rate was 4.0 l/min, conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Transcriptome analysis and quantification of intracellular sugar revealed that the amyA, MGAM, and treT involved in trehalose synthesis were upregulated, corresponding to the accumulation of intracellular trehalose under low-temperature stress. Chi et al demonstrate that corn starch can be used as the substrate for cell growth and trehalose accumulation in Saccharomycopsis fibuligera [36]. In our study, exogenous starch enhanced the tolerance of A. oryzae to low-temperature stress, implying that A. oryzae might increase the expression levels of amyA, MGAM, and treT to increase the utilization of the exogenous starch to accumulate trehalose, enhancing the adaptation to low-temperature stress.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Transcriptome analysis and quantification of intracellular sugar revealed that the amyA, MGAM, and treT involved in trehalose synthesis were upregulated, corresponding to the accumulation of intracellular trehalose under low-temperature stress. Chi et al demonstrate that corn starch can be used as the substrate for cell growth and trehalose accumulation in Saccharomycopsis fibuligera [36]. In our study, exogenous starch enhanced the tolerance of A. oryzae to low-temperature stress, implying that A. oryzae might increase the expression levels of amyA, MGAM, and treT to increase the utilization of the exogenous starch to accumulate trehalose, enhancing the adaptation to low-temperature stress.…”
Section: Discussionsupporting
confidence: 62%
“…Transcriptome analysis and quantification of intracellular sugar revealed that the amyA , MGAM , and treT involved in trehalose synthesis were upregulated, corresponding to the accumulation of intracellular trehalose under low-temperature stress. Chi et al demonstrate that corn starch can be used as the substrate for cell growth and trehalose accumulation in Saccharomycopsis fibuligera [ 36 ]. In our study, exogenous starch enhanced the tolerance of A .…”
Section: Discussionmentioning
confidence: 99%
“…So far, TCA (0.5 M), ethanol, heat shock treatment and hot water (80°C) have been used for extraction of trehalose from fungal cells [9,10,14,17]. However, none of these methods is economical, and they need a large amount of toxic TCA.…”
Section: Dmentioning
confidence: 99%
“…These yeast strains were maintained in YPD medium containing 2.0% (w/v) glucose, 1.0% (w/v) yeast extract and 2.0% (w/v) polypeptone at 4°C or in YPS medium containing 2.0% soluble starch, 1.0% yeast extract and 2.0% polypeptone at 4°C. The trehalose accumulation medium contained 100.0 ml of the hydrolysate of soybean meal supplemented with 2.0% (w/v) cassava starch [9].…”
Section: Yeast Strains and Mediamentioning
confidence: 99%
See 1 more Smart Citation